Pengaruh Ekuitas Merek terhadap Keputusan Pembelian Konsumen dalam Menggunakan Jasa Go-Jek di Kota Depok - H. Subagyo; Bintang Paula Putra; Zairin Zairin; Aminudin Aminudin; Wawan Wawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the influence of brand awareness, brand association, and brand loyalty associated with brand equity on consumer purchase decisions in using GO-JEK services in Depok City. These three variables were analyzed both partially and simultaneously to identify the degree of their influence on consumers' decisions in choosing online transportation services. The research method used is a quantitative approach with the distribution of questionnaires as a data collection instrument, while the analysis is carried out using inferential statistical techniques. The results show that partially the variables of brand association and brand loyalty have a significant and dominant influence on purchasing decisions. This indicates that consumers' perception of the image and emotional connection with the GO-JEK brand plays an important role in the decision to choose the service. In addition, the results of the simultaneous test showed that brand awareness, brand association, and brand loyalty together had a positive and significant influence on purchasing decisions. These findings confirm that strong brand equity is an important factor in increasing consumer interest and preference for GO-JEK services. Therefore, companies need to maintain and strengthen branding strategies to increase competitiveness and maintain customer loyalty.